Linear types for aliased resources - Hawblitzel, Chris (2005)
Type systems that track aliasing can verify state-dependent program properties. For example, such systems can verify that a program does not access a resource after deallocating the resource. The simplest way to track aliasing is to use linear types, which on the surface appear to ban the aliasing of linear resources entirely. Since banning aliasing is considered too draconian for many practical programs, researchers have proposed type systems that allow limited forms of aliasing, without losing total control over state-dependent properties. This paper describes how to encode one such system, the capability calculus, using a type system based on plain linear types with no special support for aliasing. Given well-typed capability calculus source programs, the encodings produce well-typed target programs based on linear types. These encodings demonstrate that, contrary to common expectations, linear type systems can express aliasing of linear resources.